Penerapan Ergonomi dan Pengelolaan Lingkungan Kerja pada UMKM Wilayah Rawan Polusi (Kubang Raya) - SRI HARDIANTI; Resy Kumalasari; M Firdaus (Jurnal Pengabdian Masyarakat Charitas, 2025)
Micro, Small, and Medium Enterprises (MSMEs) along Jalan Kubang Raya encounter substantial challenges in implementing ergonomic principles and managing workplace environmental conditions. Preliminary observations conducted on 20 MSMEs revealed that 85% of workers engaged in non-ergonomic postures 65% consistently worked in a stooped position, while 45% utilized work tables with suboptimal heights (50-60 cm). Moreover, 90% of workers were directly exposed to ambient air pollution and road traffic noise. This community engagement program was developed to enhance ergonomic awareness and improve workplace environmental conditions through four stages of intervention: (1) observation using the Rapid Entire Body Assessment (REBA) method, (2) interactive awareness sessions, (3) hands-on training in simple work tool modifications, and (4) periodic evaluation. The program outcomes demonstrated a significant increase in ergonomic comprehension (from 25% to 82% as measured by pre- and post-tests), a 45% reduction in musculoskeletal pain complaints, and the adoption of safe work practices by 78% of participants. Notably, 65% of the MSMEs independently constructed dust protection devices, contributing to a reduction in pollution exposure by up to 30%. These findings underscore the effectiveness of participatory approaches in promoting occupational health and enhancing productivity in MSMEs operating in high-risk environmental areas. For sustainability, it is recommended to establish local ergonomic cadres and integrate training modules into the programs of the regional Department of Manpower.